Fostering reading comprehension through shared reading in the year four English classroom (IR) - Sheema Ahtmanathan (2017)
The objective of this study is to identify students responses towards reading comprehension,the strategies used by the researcher to facilitate students reading comprehension and students experiences during shared reading sessions. A qualitative case study design was selected to answer three research questions. Ten year four students from a school in Cameron Highlands, Pahang participated in the study. The researcher facilitated the shared reading sessions while observed by another teacher. Six sessions of shared reading were conducted using two different big books which were recorded and transcribed. Six students were then selected for semi-structured interview sessions. The recording transcriptions, interview transcriptions and observation notes were analysed using the framework technique of thematic coding.The findings showed six categories of students responses towards reading comprehension. Overall, the students enjoyed and preferred shared reading and it enhanced their reading comprehension. The implication of this study suggested that shared reading needs to be carried out in the English classroom on a regular basis to foster reading comprehension.